Young women’s experience of personal recovery following acute myocardial infarction: A qualitative study - Cenjing Zhu; Andrew Arakaki; Alisia Pan; Karina Danvers; Andrea Barbardo; Janan Wyatt; Catherine X. Wright; Donald S. Wright; Louise Pilote; Valeria Raparelli; Joan K. Monin; Gabriele Oettingen; et al. (PLoS ONE, 2025)
Background Rates of acute myocardial infarction (AMI) morbidity and mortality have increased in young women aged ≤55 years but little is known about their experience recovering from and living with AMI. A personal recovery (experience of an identity shift manifested in both losses and gains) has been reported among general AMI survivors. Our objective was to gain insights into young women’s perspectives on long-term post-AMI recovery, under the patient-centered personal recovery framework. Methods and results The study used a participatory, phenomenological approach. In-depth interviews were conducted with 18 young women (18–55 years at the time of their AMI) who were readmitted within the first year post-AMI; these were audio-recorded, transcribed verbatim, and analyzed in collaboration with two women with lived experience of AMI. Study findings revealed that young women’s experience did not deviate largely from the personal recovery framework from the general AMI survivors (i.e., an identity shift manifested with both losses and gains). However, certain aspects in the psychosocial domain were highlighted and further articulated to address young women’s experience. Specifically, within the three categories of the personal recovery framework, two of which (i.e., loss, and gain) can be further classified, eight themes were identified around the topics of loss of safety and security, self-worth, social roles, (both the loss and gain of) hope and optimism, and gain of connection, strategies to manage emotions, and meaning and purpose. Conclusion Findings validated the utility of personal recovery framework in capturing the experience of young women with AMI, and highlighted themes that address young women’s distinguished ways of meaning-making, which anchors around social roles and personal identity. Identifying opportunities to improve awareness of self-care and facilitating social support for young women after AMI represents important targets for future intervention.